Nyutdannede jordmødres vurdering av utdanning, klinisk kompetanse og arbeidsforhold - Mari Landsverk Hagtvedt; Tine Schauer Eri (Septentrio Academic Publishing, 2015)
Newly qualified midwives' self-assessment of education, clinical competence and working conditions In Norway, post-graduate nursing programmes are being transformed into master programmes. This occurs without previous evaluation of the study programmes. The level of competence and the requirements of newly qualified are being discussed, and a mentoring programme has been suggested to ensure follow-up and development of clinical competence. In central parts of the country, newly qualified midwives have difficulties getting a permanent full time position, which affects their possibilities to develop clinical competence. An evaluation study of the midwifery program at Vestfold University College has been performed to assess its relevance for professional work, as well as mapping the respondents' working conditions and their self-assessment of clinical competence. The method used was a survey. The respondents rate the program as good. They lack competence to manage complicated conditions related to the perinatal period, and are inadequate when it comes to issues related to women's sexual heath. These midwives work part-time, and it may take years to get a permanent position. They rate the follow-up as newly qualified as satisfying, yet they do not feel sufficiently confident during clinical practice. Comprehensive national midwifery competence will require more full time positions and better follow-up of newly qualified. To lay the basis for the content in master programmes, there is a need for a national evaluation of the midwifery programmes and a review of the professional competence of newly qualified.